Experimental Investigation of Both SCC and Rubberized Concrete Beams with Vertical Openings - Mohamed Emara; Heba A. Mohamed; Mostafa S. Rizk (International Journal of Concrete Structures and Materials)
Abstract Reinforced concrete (RC) beams with vertical openings are becoming more frequent in new construction to transport numerous services, particularly in structures with restricted height and size. A significant lack of studies was observed to investigate the influence of a vertical opening in the shear zone on the RC beams' behavior and performance. This research investigated experimentally the performance of RC beams with vertical openings at the shear zone, whether these beams were cast with self-compacting concrete (SCC) or rubberized concrete (RUC). In addition, the purpose of this work is to compare the influence of steel fiber (SF) on the performance of vertically perforated SCC beams with its influence on the performance of vertically perforated RUC beams. The impact of the number of vertical openings and the SF ratio used in beam specimens on the beam behavior, including compressive and tensile strengths, crack patterns and modes of failure, maximum deflection, stiffness, loading capacity, and ductility, was evaluated in the current paper. The experimental findings demonstrated that the existence of vertical openings at the shear zone of SCC and RUC beams resulted in a decrease in stiffness with ratios ranging from 10.43 to 66.98%, maximum loading capacity with ratios ranging from 10.66 to 37.73%, and ductility index with ratios ranging from 2.14 to 21.53% compared to the solid beams. It also has a tangible impact on raising the maximum mid-span deflection at the ultimate load, ranging from 2.03 to 81.64%. Moreover, when the number of vertical openings increased, the cracks increased at the shear span in which the openings were located. In general, adding SF to the SCC mixture showed a more significant effect on enhancing the tensile and compressive strengths, stiffness, and ultimate load compared to that in the case of the RUC. For example, the stiffness and ultimate load of the solid SCC beam with a SF ratio of 1% increased by 164.58% and 70.19%, respectively, compared to the solid SCC beam without SF, while those of the solid RUC beam with the same ratio of SF increased by 69.91% and 61.85%, respectively.